Airline routes and second home tourism. The french market in the Algarve - Ribeiro de Almeida, Cláudia (Journal of Tourism, Sustainability and Well-being, 2018)
The new routes and services provided by low cost carriers enable the emergence of new tourist destinations in Europe and the development of new market segments that value the cheap and easy air accessibilities. One of the best examples is second home tourism (normally associated with residential tourism) that grew in recent years, mainly in tourism destinations in the south of Europe and Mediterranean. One of them is the Algarve that receive nowadays new second home owners coming from several countries, mainly because of the region’ great weather conditions, security and air accessibilities. France is one of the new second home market in Algarve, mainly because of the new Non-Habitual Residents (NHR) regime, that provides to new residents a very attractive tax benefits for their 10 years living in Portugal, as well as the new routes provided by low cost carriers since 2016 to eleven airports of France.